ANALYSIS OF INDONESIA STATE BUDGET AND THE REALITY OF DEFICIT AND BUDGET EFFICIENCY - Iskandar Muda; Andy Mulia; Safira Putri Adity; Adelya Soffy Sembiring; Arifin Wahyudi Hasibuan (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
The State Budget (APBN) plays a crucial role in managing fiscal policy and supporting national development in Indonesia. This study aims to analyze the realistic condition of Indonesia’s state budget, focusing on the persistent budget deficit and inefficiencies in government spending. A qualitative descriptive method is used by examining secondary data from official reports and relevant literature. The findings show that Indonesia continues to experience a budget deficit, leading to a reliance on debt financing. In addition, the budget is highly dependent on tax revenue, while inefficiencies in public spending and poorly targeted subsidies, particularly in fuel subsidies, remain significant issues. These conditions reduce fiscal space & limit the government’s ability to allocate funds to productive sectors such as education and healthcare. The study concludes that improving budget efficiency requires comprehensive reforms, includi ng tax system improvements, better subsidy targeting, increas ed tran sparency & more prudent debt management. These efforts are essent ial to ensure sustainable fiscal policy and maximize public welfare.